Going to Court to Change Japan Social Movements and the Law in Contemporary Japan - Steinhoff, Patricia G. (Michigan Monograph Series in Japanese Studies, 2016)
"Going to Court to Change Japan takes us inside movements dealing with causes as disparate as death by overwork, the rights of the deaf, access to prisoners on death row, consumer product safety, workers whose companies go bankrupt, and persons convicted of crimes they did not commit. Each of the six fascinating case studies stands on its own as a detailed account of how a social movement has persisted against heavy odds to pursue a cause through the use of the courts. The studies pay particular attention to the relationship between the social movement and the lawyers who handle their cases, usually pro bono or for minimal fees. Through these case studies we learn much about how the law operates in Japan as well as how social movements mobilize and innovate to pursue their goals using legal channels. The book also provides a general introduction to the Japanese legal system and a look at how recent legal reforms are working. Going to Court to Change Japan will interest social scientists, lawyers, and anyone interested in the inner workings of contemporary Japan. It is suitable for use in a wide range of undergraduate and graduate courses on Japan in social sciences and law, and can also provide a comparative perspective to general courses in these fields. Contributors include John H. Davis Jr., Daniel H. Foote, Patricia L. Maclachlan, Karen Nakamura, Scott North, Patricia G. Steinhoff, and Christena Turner."